Electrode Processes in Electrochromic Anodic Oxide Films on Niobium (JOURNAL OF ADVANCES IN CHEMISTRY, 2018)
We review the following issues: peculiarities of polycrystalline AOP development at niobium in nitrate salt melt at temperatures of Nb2O5 recrystallization, the mechanisms of change in structure and properties of niobium pentoxide in the result of electrode processes under cathodic polarization (at the model structure of polycrystalline film), as well as the methods of amorphous electrochromic AOP development and ways of electrochromic processes optimization at such films.